(3TQM TeS GdEcSjQs - (3Ydj Hf eMeO Hf CjOeQ GdpLrdnOcj, YR GdOjf,J (B742 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI gPG cJGH TQM TeS GdEcSjQ ddMdhcj ai GdJQGcjH dHdbjGS GdMcje bGd HdbjGS Gf GdbOeGA ef GdMceGA hCTGQhG HgG Edi eYGfj cKjQI cGfhG jSeYhfgG hMjG s
(3BNQgG (B:s
(3bO cedJ cJGH TeS GdCcSjQ s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B28s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs